2023
DOI: 10.1002/smll.202300309
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Index‐Adaptive Nanoporous Chiral Photonic Crystal Film for Chemical Detection Visualized via Selective Reflection

Abstract: Photonic crystals (PC) are of great importance in technology, especially in optics and photonics. In general, the structural color of PCs responds to external stimuli primarily by changing their periodicity. Herein, the authors report on refractive index (RI) adaptive PCs. Cross‐linked cholesteric films with interconnected nanopores exhibit a very low RI without light scattering. Transparent PC films with maximum reflectance in the ultravoilet (UV) region respond to various chemicals by changing the reflective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…1 and 2a ). Compared with the film before washing, the PBG of the SPC film exhibited a blueshift due to the pitch change caused by the absence of liquid crystal molecules 38 . The texture of the SPC S film remained the same after removing the unpolymerized material (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2a ). Compared with the film before washing, the PBG of the SPC film exhibited a blueshift due to the pitch change caused by the absence of liquid crystal molecules 38 . The texture of the SPC S film remained the same after removing the unpolymerized material (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the absorption peak center of PBG was at 380 nm, which closely coincided with the EBG of 6% FT. Because light with a wavelength of 380 nm corresponded to blue light, the SOPC film appeared bright light blue under natural light. 70 The SOPC was denoted as SOPC-380.…”
Section: Morphology and Optical Properties Of Sopc Film And X% Ft/sop...mentioning
confidence: 99%
“…[15] Its unique photonic band gap (PBG) can reflect light at a specific wavelength, so when PBG is in the visible range, the structural color will appear. [16,17] Furthermore, when the refractive index (RI) or thickness of PCs is changed by external stimuli, the PBG position will shift, causing color changes of the PCs, thus converting stimuli into visual detection. [18,19] In view of the sensitivity of human vision to color, this detection method using color transformation to visualize external stimuli has shown great advantages in the field of sensing.…”
Section: Introductionmentioning
confidence: 99%